Antioxidant Activity and Toxicity Tests of Panahan Leaf Extract (Ayapana triplinervis (Vahl) RM) against Shrimp Larvae ( Artemia salina Leach) - Daniel, Daniel; Maygusten, Maygusten; Gunawan, Rahmat; Magdaleni, Agustina Rahayu (Universitas Syiah Kuala, 2023)
Research on the antioxidant activity test and toxicity test of leaf extract (Ayapana triplinervis (ValH) RM) has been conducted against the larval shrimp (Artemia salina Leach). The dried leaves weighing 500 grams were macerated using methanol, filtered, and concentrated using a rotary evaporator. Methanol crude extract was fractionated with n-hexane, ethyl acetate, and methanol water. Based on Test Phytochemicals screening on secondary metabolites showed that the crude extract of methanol, n-hexane fraction, and methanol-water containing secondary metabolites alkaloids, flavonoids, and phenolic in ethyl acetate fraction of the content of secondary metabolites, alkaloids, and flavonoids, and the fraction of n-hexane and ethyl acetate contain steroids. In contrast, the crude extract of methanol and n-hexane fraction contains phenolic compounds. Test mortality of shrimp larvae (Brine Shrimp Lethality Test) showed mortality of shrimp larvae (Artemia salina Leach) using Probit analysis (SAS) to determine the value of 50% Lethal Concentration (LC50). In this test, the most active is the methanol crude extract of archery leaves, with a value of 18.8608 ppm, in a test of antioxidant activity using DPPH free radical reduction in the spectrophotometer and IC50 values obtained. In methanol crude extract was 430.73 ppm; n-hexane fraction was 168.5 ppm; ethyl acetate fraction was 114.87 ppm; and methanol-water fraction was 37.23 ppm